Conscientious Avoidance: How Knowledge in the Prosecutorial System Shapes Indonesia’s Transition? - Harison Citrawan; Nurrahman Aji Utomo (Sriwijaya Law Review, 2025)
The prevailing view in transitional justice studies suggests that Indonesia is experiencing a political transition without justice. In this article, we attempt to examine the conscientious avoidance of criminal prosecution of past gross human rights violation cases. Through the lens of sociology of punishment, we identify three factors that shape this current penal decision: the knowledge and domination in the penal system, the human rights-focused criminal victim protection and the welfare assistance as a symbolic reparation aimed at neutralising past atrocity crimes. This research employs a narrative approach under the discipline of socio-legal studies. This article contends that the decentralised structure of knowledge within the penal system reflects the dominance and authority in penal decisions, which consist of competing groups and interests. This complexity poses challenges at the institutional level in transforming the political motives behind past atrocities into criminal justice knowledge. The evolving nature of this knowledge within the country’s penal system indicates a future path for the prosecution of past atrocity crimes.